A single-ion magnet building block strategy toward Dy2 single-molecule magnets with enhanced magnetic performance. Issue 48 (30th November 2022) - Shao, Dong; Sahu, Prem Prakash; Tang, Wan-Jie; Zhang, Yang-Lu; Zhou, Yue; Xu, Fang-Xue; Wei, Xiao-Qin; Tian, Zhengfang; Singh, Saurabh Kumar; Wang, Xin-Yi
Abstract : A dysprosium(iii ) single-ion magnet (SIM) was used as a building block for the construction of dinuclear lanthanide single-molecule magnets (SMMs). Abstract : A molecular dysprosium(iii ) complex [Dy(DClQ)3 (H2 O)2 ] (1 ) was used as a building unit for the construction of lanthanide SMMs, leading to the isolation of two dinuclear Dy(iii ) complexes, namely [Dy2 (DClQ)6 (MeOH)2 ] (2 ) and [Dy2 (DClQ)6 (bpmo)2 ]·6MeCN (3 ) (DClQ = 5, 7-dichloro-8-hydroxyquinoline, bpmo = 4, 4′-dipyridine-oxide). Structural analyses revealed the same N3 O5 coordination environment of the Dy(iii ) centers with a distorted biaugmented trigonal prism ( C 2V symmetry) and triangular dodecahedron ( D 2d symmetry) for 2 and 3, respectively. Magnetic studies revealed the presence of ferromagnetic and weak antiferromagnetic exchange interactions between the Dy 3+ centers in 2 and 3, respectively. Interestingly, slow relaxation of magnetization at zero fields was evidenced with an U eff of 51.4 K and 159.0 K for complexes 2 and 3, respectively. The detailed analysis of relaxation dynamics discloses that the Orbach process is dominant for 2 whereas Raman and QTM play an important role in 3 . Theoretical calculations were carried out to provide insight into the magnetic exchange interactions and relaxation dynamics for the complexes. Due to a single-ion magnet (SIM) of 1, the foregoing results demonstrate a SIM modular synthetic route for the preparation of dinuclear lanthanide SMMs.